Novel expert system for defining power quality compensators - Liberado, Eduardo Verri; Marafao, Fernando Pinhabel [UNESP]; Simões, Marcelo Godoy; Souza, Wesley Angelino de; Pomilio, José Antenor (Elsevier B.V., 2015)
In order to ensure good power quality for modern power systems and/or industrial installations, power conditioning devices have been extensively applied. However, the data analysis for the installation of a determined compensator mainly considers a particular power quality index or disturbance and it is usually based on human expertise. Therefore, this paper proposes a novel expert system that automatically suggests the most appropriate and cost-effective solution for compensating reactive, harmonic and unbalanced current through a careful analysis of several power quality indices and some grid characteristics. Such an expert system is an important tool in real-world applications, where there is a complex scenario in choosing, designing and applying power quality compensators in modern power grids. Since there are no strict boundaries for voltage and current non idealities at distribution level or clear correlation between them and possible solutions, a fuzzy decision-maker was developed to deal with such uncertainties and to embed human expertise in the system. The approach is based on analyzing data from a given time window and providing off-line recommendations for the design and installation of proper compensators. Therefore, the application of the proposed expert system may result in enhanced and faster projects when compared to the traditional design methods for power conditioning. A computational study consisting on applying the suggested compensators for a 5-node network and different load configurations shows the effectiveness of the proposed expert system. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Compensation; Decision-maker; Expert system; Harmonic distortion; Load unbalance; Power factor correction; Power quality